ANALISIS MATERI PADA BUKU AJAR S’IL VOUS PLAÎT UNTUK TINGKAT A1 - Zakiah, Cindy; Indri Hardini, Tri; Widawati, Rika (LPPM Universitas PGRI Silampari Lubuklinggau, 2024)
One way to assist students in the language learning process is by using textbooks. There is a difference in learning achievement before and after implementing literacy-based thematic textbooks with a contextual approach for students. This study aims to determine the quality and relevance of the content used in the teaching and learning process. The method employed in this research is qualitative descriptive method by analyzing the content and describing data regarding the suitability of A1 level material based on the CECRL assessment in the textbook